Ecological and chemical characteristics of small river Arguzikha (Zeya-Bureya plain, Russia) - Pakusina Antonina; Platonova Tatyana (E3S Web of Conferences, 2020)
The article considers the results of research from 2015 to 2019 on the study of hydrochemical indicators and the content of heavy metals in the ecosystem components of the small Arguzikha river , a left-Bank tributary of the Amur river (water, bottom sediments, macrophytes, birds ’ feathers). High oxygen content in the water (8.8-15.9 mgO2/dm3) and high BOD5 values (6-12 mgO2/dm3) in the middle and lower reaches of the Arguzikha river indicate the process of eutrophication. The value of permanganate oxidability (6.8-15.5 mgO/dm3) characterizes the high content of organic substances in water. In the spring, nitrate nitrogen (3.45-6.39 mgN-NO3-/dm3) was found in the water of the Arguzikha river, which had a pyrogenic origin. In the summer the rainy season was dominated by ammonium nitrogen (2.34 mgN-NН +/dm3). The high content of total phosphorus (0.337-0.609 mg/dm3) in the river water was in the spring. In the spring of 2015, the concentration of lead in the lower reaches of the river reached 6.36 µg/dm3, during the subsequent time, the lead content in the Arguzikha water was less than the MPC. Toxic concentrations of lead (> 30 mg / kg) and manganese (> 300 mg/kg) were found in macrophytes of Nymphoides peltata and Myriophyllum spicatum. In the feathers of waterfowl of the Arguzikha river the content of heavy metals decreases in a row Fe>Zn>Cu>Pb>Mn>Сг>Ni>Cо>Cd. The feathers of Anas acuta and Anas querquedula contained Pb 17.7 mg/kg and 22.2 mg/kg, Cd 0.15 mg/kg and 0.08 mg/kg, respectively.